Insulin autoimmune syndrome (Hirata Disease): Case report in a saudi female patient with graves' disease and literature review - Almutairi, Mohammed; Aljumah, Hazem (Journal of Diabetes and Endocrine Practice, 2020)
Uncommon scenario of spontaneous hypoglycemia after starting carbimazole due to insulin autoimmune syndrome, characterized by high levels of insulinemia and circulating autoantibodies to insulin without prior insulin administration. So far, in Western countries, <70 cases have been published. In addition, more than 380 cases of this syndrome have been reported.
Keywords: Hirata disease; hypoglycemia; hypoglycemia induce by carbimazole; insulin autoimmune syndrome; insulinoma differential diagnosis; insulinoma mimics